Programming Languages and Systems 27th European Symposium on Programming, ESOP 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Ahmed, Amal (Theoretical Computer Science and General Issues,, 2018)
This book is Open Access under a CC BY licence. .